Study on Water quality of Narmada River by analyzing physicochemical and biological parameters using random forest model - Gour, Sanjeev; Gour, Mamta (International Journal of Computer Sciences and Engineering, 2019)
Rivers are most important recourse for consumption as freshwater for human being. The quality of water resource can be measured and indentified by its physicochemical and biological parameters. This paper presents a study of water quality of River Narmada through analysis of some of its selected physicochemical and biological parameters. For this study, secondary dataset with 7 water quality parameters collected during years from 1990 to 2012 of River Narmada of Hoshangabad district of Madhya Pradesh has been used. The objective of this study to assess the quality of water of Narmada River in comparison with Surface Water Quality Standards for Indian Rivers. For this assessment, one of algorithm of data mining called random forest is used which is incorporate as built in model of an analytical tool called Rapid Miner. This study show that quality of river water is not favorable and goes down day by day due to domestic and industrial effluents mixing in the river at town. The finding of this study gives definitely an alert message to water resource managers for the improvement of water quality management by proper treatment and monitoring the River.